Correction: Dietary riboflavin deficiency induces genomic instability of esophageal squamous cells that is associated with gut microbiota dysbiosis in rats. Issue 12 (19th November 2020) - Pan, Feng; Xu, Xin; Zhang, Ling-Li; Luo, Hong-Jun; Chen, Ye; Long, Lin; Wang, Xuan; Zhuang, Pei-Tong; Li, En-Min; Xu, Li-Yan
Abstract : Correction for 'Dietary riboflavin deficiency induces genomic instability of esophageal squamous cells that is associated with gut microbiota dysbiosis in rats' by Feng Pan et al., Food Funct., 2020, DOI: ; 10.1039/d0fo01944e .